Clinicopathological Factors Affecting Survival and Recurrence after Initial Hepatectomy in Non-B Non-C Hepatocellular Carcinoma Patients with Comparison to Hepatitis B or C Virus. (13th March 2014) - Okuda, Yoshihiro; Mizuno, Shugo; Shiraishi, Taizou; Murata, Yasuhiro; Tanemura, Akihiro; Azumi, Yoshinori; Kuriyama, Naohisa; Kishiwada, Masashi; Usui, Masanobu; Sakurai, Hiroyuki; Tabata, Masami; Yamada, Tomomi; et al.
Abstract : We evaluated clinicopathological factors affecting survival and recurrence after initial hepatectomy in non-B non-C (NBNC) hepatocellular carcinoma (HCC) patients with comparison to hepatitis B or C virus, paying attention to relationship between alcohol consumption and histopathological findings. The medical records on the 201HCC patients who underwent initial hepatectomy between January 2000 and April 2013 were retrospectively reviewed. NBNC patients had higher prevalence of hypertension (47.4%), diabetes mellitus (35.5%), alcohol consumption (>20 g/day) (61.8%), and preserved liver function than hepatitis B or C patients. The 5-year survival rate of NBNC patients (74.1%) was significantly better than hepatitis B (49.1%) or C (65.0%) patients (NBNC versus B, P = 0.031 ). Among the NBNC patients, there was no relationship between alcohol consumption and clinicopathological findings including nonalcoholic fatty liver disease activity score (NAS). However, the 5-year OS and RFS rates in the alcohol-unrelated NBNC patients tend to be better than in the alcohol-related. By multivariate analysis, independent factors for OS in NBNC patients were Child-Pugh B/C, intrahepatic metastasis (im), and extrahepatic recurrence. NBNC patients, who were highly associated with lifestyle-related disease and preserved liver function, had significantly better prognosis compared to hepatitis B/C patients; however, there was no association between alcohol consumption and histopathological findings.